Synthesis, spectroscopic characterization and quantum chemical computational studies on 4-(3-methyl-3-phenylcyclobutyl)-2-(2-undecylidenehydrazinyl)thiazole - Sen, Fatih; Dincer, Muharrem; Cukurovali, Alaaddin (Elsevier, 2014)
The Schiff base compound, 4-(3-methyl-3-phenylcyclobutyl)-2-(2-undecylidenehydrazinyl)thiazole, (C25H37N3S), was synthesized and characterized combining several experimental techniques (X-ray, H-1 NMR and C-13 NMR) and theoretical methods. The compound crystallizes in the monoclinic space group P 2(1)/c with a =16.2306 (6) angstrom, b = 6.728 (2) angstrom, c = 26.1834 (10) angstrom, beta = 120.687 (3), and Z = 4. The initial molecular geometry (X-ray coordinates) was optimized using Hartree Fock (HF) and Density Functional Theory (DFT/B3LYP) method with the 6-31+G(d, p) basis set in ground state. From the optimized geometry of the molecule, geometric parameters, vibrational frequencies, gauge-independent atomic orbital (GIAO) H-1 and C-13 NMR chemical shift values of the title compound have been calculated theoretically and compared with the experimental data. Data from theoretical calculations show excellent consistency with experimental results. Besides, molecular electrostatic potential (MEP) distribution, frontier molecular orbitals (FMOs) and non-linear optical (NLO) properties of the title molecule were investigated by theoretical calculations. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Schiff base; X-ray structure determination; Molecular modelling; IR and NMR spectroscopy; Molecular electrostatic potential (MEP); Non-linear optical properties